2015
DOI: 10.1039/c5lc00616c
|View full text |Cite
|
Sign up to set email alerts
|

Guiding pancreatic beta cells to target electrodes in a whole-cell biosensor for diabetes

Abstract: We are developing a cell-based bioelectronic glucose sensor that exploits the multi-parametric sensing ability of pancreatic islet cells for the treatment of diabetes. These cells sense changes in the concentration of glucose and physiological hormones and immediately react by generating electrical signals. In our sensor, signals from multiple cells are recorded as field potentials by a micro-electrode array (MEA). Thus, cell response to various factors can be assessed rapidly and with high throughput. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…According to the physiology of pancreatic islets, β-cells sense glucose, metabolize it to secrete insulin, and are nevertheless electrically excitable. In fact, during the multistep process of glucose metabolism, ATP is produced, which in turn controls the opening and closure of specific ion channels and triggers well-defined ion fluxes that generate an electrical current [ 145 , 146 ]. The electrical signals produced from pancreatic islets are of two types: short-lived high-frequency action potentials (AP) that reflect single cell depolarization and longer lived changes in field potentials, named “low frequency slow potentials” (SP) [ 147 ].…”
Section: Biosensors For Measuring Ooc’ Electrical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the physiology of pancreatic islets, β-cells sense glucose, metabolize it to secrete insulin, and are nevertheless electrically excitable. In fact, during the multistep process of glucose metabolism, ATP is produced, which in turn controls the opening and closure of specific ion channels and triggers well-defined ion fluxes that generate an electrical current [ 145 , 146 ]. The electrical signals produced from pancreatic islets are of two types: short-lived high-frequency action potentials (AP) that reflect single cell depolarization and longer lived changes in field potentials, named “low frequency slow potentials” (SP) [ 147 ].…”
Section: Biosensors For Measuring Ooc’ Electrical Activitymentioning
confidence: 99%
“…In particular, SPs consist of a summation of single cell activity and reflect intraislet coupling, which represents a major index of physiological quality in insulin secretion [ 148 , 149 , 150 , 151 ]. Moreover, SPs carry information about glucose concentration, with their frequency being directly correlated to the nutrient concentration: for instance, Pedraza et al proved that, in murine islets, SPs are almost absent at low glucose (3 mM) levels, while their frequency increases for higher glucose (15 mM) stimulation [ 145 ]. Furthermore, Lebreton et al found a positive correlation between SP frequencies and glucose concentration in murine islet cells, as well as in human islets [ 148 ].…”
Section: Biosensors For Measuring Ooc’ Electrical Activitymentioning
confidence: 99%
“…Tools are available for optical imaging of voltage responses, which enables high-throughput analyses of thousands of cells and will therefore likely supplant traditional electrophysiology for the characterisation of in vitro derived cells. Highthroughput electrophysiology and lab-on-a-chip technologies will be particularly useful in both understanding the phenotypic range of human islet cells and assessing their in vitro differentiated counterparts side by side [58][59][60]. The islet biologists and mathematical modellers who are most familiar with these aspects of beta cell behaviour should be engaged in studies of in vitro differentiated cells to dissect the properties of all of the major ion currents, the shape of the action potentials and the distinctive bursting patterns that are normally seen in healthy beta cells (Fig.…”
Section: Remaining Obstacles-deep Phenotypingmentioning
confidence: 99%
“…The glucose biosensing detection system composed of bio-sensing detection conversion and peripheral electronic systems can be applied to monitor the glucose concentration of diabetic patients in time. In particular, biosensing detection conversion plays a very important role in the sensing system, which determines several key factors, such as accuracy, detection time and system cost [7][8][9]. A biosensor can convert different concentrations of glucose into corresponding electrical signals for output, which has advantages of high accuracy, fast analysis, low cost, good repeatability, simple operation and high specificity by comparing with traditional detection methods [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%